The transient receptor potential channels in rheumatoid arthritis: Need to pay more attention - Niu, Mengwen; Zhao, Feng; Chen, Rui; Li, Ping; Bi, Liqi (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is characterized by the augment of vascular permeability, increased inflammatory cells infiltration, dysregulated immune cells activation, pannus formation and unbearable pain hyperalgesia. Ca2+ affect almost every aspect of cellular functions, involving cell migration, signal transduction, proliferation, and apoptosis. Transient receptor potential channels (TRPs) as a type of non-selective permeable cation channels, can regulate Ca2+ entry and intracellular Ca2+ signal in cells including immune cells and neurons. Researches have demonstrated that TRPs in the mechanisms of inflammatory diseases have achieved rapid progress, while the roles of TRPs in RA pathogenesis and pain hyperalgesia are still not well understood. To solve this problem, this review presents the evidence of TRPs on vascular endothelial cells in joint swelling, neutrophils activation and their trans-endothelial migration, as well as their bridging role in the reactive oxygen species/TRPs/Ca2+/peptidyl arginine deiminases networks in accelerating citrullinated proteins formation. It also points out the distinct functions of TRPs subfamilies expressed in the nervous systems of joints in cold hyperalgesia and neuro-inflammation mutually influenced inflammatory pain in RA. Thus, more attention could be paid on the impact of TRPs in RA and TRPs are useful in researches on the molecular mechanisms of anti-inflammation and analgesic therapeutic strategies.